Investigating the Fate of Tetracycline in an Anaerobic Membrane Bioreactor and Its Effects on Antibiotic Resistance Gene Proliferation from Different Membrane Types - Zeeb, Reem (2022)
As the concern of fresh and clean water scarcity is raised worldwide, the necessity of water reuse stands out. In this sense, the AnMBR, an advanced wastewater treatment technology combining the advantages of the MBR and anaerobic processes, has gained much attention in the past years as it produces high quality effluent from an energy efficient mechanism. Even though the removal of emerging microbial contaminants generally and antibiotics specifically from wastewater has been studied, the reduction of ARGs and tetracycline, which is one of the most used antibiotics worldwide, hasn’t been explicitly looked into using AnMBRs during treatment of real municipal wastewaters. Hence, this research, composed of a pre-tetracycline addition phase and a tetracycline addition phase, aimed to examine the effect of tetracycline continuously fed at a concentration of 300 μg/L on the performance of a lab-scale AnMBR as well as to evaluate the removal efficiency of tetracycline via the AnMBR system while looking into the attribution of each removal mechanism. It also studied the proliferation of iARGs and eARGs in the effluents of three externally connected membranes: two MFs and one UF. The results showed that a slight and quickly recoverable disruption was imposed by tetracycline on the system. Tetracycline was reduced at an efficiency > 91% for the three effluents with adsorption to sludge being the primary mechanism of removal even though notable degradation averaged to 38 % was recorded. The contribution of adsorption of tetracycline to the biofilm layer developed on each of the three membranes to removal was negligible. For ARGs, an increase in the abundance of tet-associated iARGs, with variation depending on the membrane pore size, was detected in the effluent, in opposition to tet-associated eARGs and non-tet ARGs which did not show an interpretable response to tetracycline.